Noise and Oil Viscosity Characterization and Modelling for Petrol-Gas-Converted Generator (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The modification of petrol generators to operate on dual-fuel systems such as petrol-gas offers advantages in fuel efficiency and emission reduction, but it also introduces new challenges in maintenance, particularly in noise behavior and oil degradation. This study presents a comprehensive characterization and modelling of noise levels and oil viscosity in a petrol-gas-converted generator under various load conditions and operational durations. Experimental data were collected using a digital sound level meter and a Brookfield viscometer at intervals over a 60-hour runtime. An Artificial Neural Network (ANN) model was developed in MATLAB using a feedforward backpropagation architecture with a 70:15:15 training-validation-testing split. The ANN model achieved high predictive accuracy, with R² values of 0.9 for prediction of for oil viscosity based on noise level. The results demonstrate that ANN-based modelling provides a reliable approach for forecasting the operational variables on petrol-gen-converted generators. These findings offer a valuable tool for predictive maintenance and performance optimization in hybrid-fuel power systems.